Feline hyperthyroidism: diagnosis and treatment - KASABALIS (Δ. ΚΑΣΑΜΠΑΛΗΣ), D.; SOUBASIS (Ν. ΣΟΥΜΠΑΣΗΣ), N.; PETANIDES (ΠΕΤΑΝΙΔΗΣ Θ.Α.), T. A. (Journal of the Hellenic Veterinary Medical Society, 2017)
Hyperthyroidism is a common endocrinopathy in cats older than 8 years, with no sex or breed predisposition. Benign adenomas and adenomatous hyperplasia of the thyroid gland is observed in the majority of cases. Symptoms reflect the effect of thyroid hormone excess in various systems, with weight loss, polyphagia, polyuria-polydipsia, cardiovascular and gastrointestinal abnormalities being common clinical manifestations. On clinical examination, there is frequently prominent thyroid enlargement. Common laboratory abnormal findings include increased activity of alkaline phosphatase and alanino-aminotransferase, hyperphosphataemia, azotaemia and decreased concentration of ionized calcium and creatinine. Definite diagnosis of the disease is based on the demonstration of increased blood concentration of thyroid hormones. Measurement of thyroxine concentration, alone or in conjunction with concentration of free thyroxine, is usually sufficient to reach a diagnosis. When diagnosis is uncertain, thyroid stimulating hormone, scintigraphy and dynamic function tests can be used. The possibility of concurrent diseases (e.g., renal failure, diabetes mellitus) must be investigated, as their presence has implications on diagnosis and treatment. Medical therapy, thyroidectomy, radionine therapy and low iodine diet are also valid options for treatment. Each has advantages and disadvantages that a clinician must take into consideration before instigating treatment. Prognosis for hyperthyroidism is favourable if no severe disease exists concurrently.